PENGGUNAAN EMOJI FOOD SEBAGAI PREDIKTOR PENENTUAN STATUS GIZI BALITA USIA 3-5 TAHUN DI DESA KUBU KECAMATAN KUBU KABUPATEN KUBU RAYA - Aji, Ade Nugraha; Jaladri, Iman (Pontianak Nutrition Journal, 2018)
Nutritional problems are the impact of consumption of nutrients that have not met the body’s needs. Poor intake can cause malnutrition, and vice versa. To find out nutritional intake, a food consumption survey is needed. The current food consumption survey still has some weaknesses when used in describing nutritional status. Researchers make a method called emoji food. Emoji food is a method used to express the perception of eating habits. Emoji food in the form of symbols adapted from emojis in the android smartphone chat application. The purpose of this study was to determine the relationship between the use of Emoji food as a predictor of the determination of nutritional status of children aged 3-5 years in Kubu Village, Kubu District, Kubu Raya Regency. This study entered into the category of observational analytic research with a cross sectional approach where the measurement of the variables was carried out simultaneously from the individual in a single population and the measurement was only carried out at one time or period. From the results of the research BB/TB = Sig. (2-tailed) <5% (0.001 <0.05) which means BB/TB has a relationship with Emoji Food. BB/U value = Sig. (2-tailed) <5% (0.007 <0.05) which means BB/U has a relationship with Emoji Food. IMT/U Sig value. (2-tailed) <5% (0.001 <0.05) which means IMT/U has a relationship with Emoji Food. The conclusion of this study is the relationship of each of the variables of nutritional status, namely between BB/TB, BB/U, and IMT/U with the use of Emoji Food in children aged 3-5 years in Kubu Village, Kubu District, Kubu Raya District. Suggestions from this study Emoji food can be used as an alternative used in assessing and providing an overview of nutritional status.